Tuning to the band gap by complex defects engineering: insights from hybrid functional calculations in CuInS2. (14th December 2017) - Yang, Pei; Shi, Li-Jie; Zhang, Jian-Min; Liu, Gui-Bin; Yang, Shengyuan A; Guo, Wei; Yao, Yugui
Abstract: Tuning band gaps of semiconductors in terms of defect control is essential for the optical and electronic properties of photon emission or photon harvesting devices. By using first-principles calculations, we study the stability condition of bulk CuInS2 and formation energies of point and complex defects in CuInS2 with hybrid exchange-correlation functionals. We find that at Cu-rich and In-poor conditions, 2Cui + CuIn is the main complex defect, while InCu + 2VCu is the main complex defect at In-rich and Cu-poor conditions. Such stable complex defects provide the feasibility of tuning band gaps by varying the [Cu]/[In] molar ratios. These results present how the off-stoichiometry CuInS2 crystal structures, and electronic and optical properties can be optimized by tuning the [Cu]/[In] ratio and Fermi level, and highlight the importance of complex defects in achieving better photoelectric performance in CuInS2 . Such band gap tuning in terms of complex defect engineering is a general approach and thus applicable to other photo-harvest or light-emission semiconductors.